2015
DOI: 10.1038/onc.2015.145
|View full text |Cite
|
Sign up to set email alerts
|

The nucleotide excision repair protein XPC is essential for bulky DNA adducts to promote interleukin-6 expression via the activation of p38-SAPK

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are environmental pollutants, and many are potent carcinogens. Benzo[a]pyrene (B[a]P), one of the best-studied PAHs, is metabolized ultimately to the genotoxin anti-B[a]P-7,8-dihydrodiol-9,10-epoxide (BPDE). BPDE triggers stress responses linked to gene expression, cell death and survival. So far, the underlying mechanisms that initiate these signal transduction cascades are unknown. Here we show that BPDE-induced DNA damage is recognized by DNA damage sensor proteins to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…1b and Supplementary Figure 4b ). It was recently shown that XPC knockdown decreases the activation of p38 after UV light 31 . Notably, we found that knockdown of CSB or XPC resulted in decreased binding of 14-3-3 to NELFE, which is in agreement with the reduced activation of p38 in these cells and suggests that the interaction is partially dependent on the DNA damage recognition by the NER machinery (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1b and Supplementary Figure 4b ). It was recently shown that XPC knockdown decreases the activation of p38 after UV light 31 . Notably, we found that knockdown of CSB or XPC resulted in decreased binding of 14-3-3 to NELFE, which is in agreement with the reduced activation of p38 in these cells and suggests that the interaction is partially dependent on the DNA damage recognition by the NER machinery (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8-oxo-guanine) (14)(15)(16). In addition to the role of XPC during DNA repair, it was, like several other NER proteins, ascertained at promotor regions of genes activated by nuclear receptors (17) and XPC was recently shown to promote p38-SAPK dependent gene expression under inflammatory conditions (18).…”
Section: Resultsmentioning
confidence: 99%
“…This function is independent of DNA damage and can influence the expression of hundreds of genes ( Bidon et al, 2018 ). XPC is also involved in the transcription of nuclear receptor genes, has a putative function in base excision repair, and promotes cytokine release in response to benzo[a]pyrene-7,8-dihydrodiol-9,10-epoxide (BPDE) adducts in DNA ( Fong et al, 2013 ; Schreck et al, 2016 ). The relative insensitivity of XPC cells to the effects of glucose ( Figs 2 and 5 ) was attributed to loss of its multiple functions.…”
Section: Discussionmentioning
confidence: 99%